Cultural policy through the prism of fiction (Michel Houellebecq). Issue 1 (2nd January 2017) - Ahearne, Jeremy
Abstract : Cultural policy studies tends to talk about fiction without actually using it. A typical move is to place it in an aesthetic realm to be protected, situated and/or critiqued. This is an eminently worthwhile activity. However, this paper explores some ways in which works of fiction may, following their own dynamic, yield significant perspectives upon the world of cultural policy itself. In what ways do fictional works offer us prisms through which to reappraise the worlds of cultural policy? What are the effects of the reconfigurative imaginative play to which they subject the institutions of that world? How are the discourses of cultural policy reframed when redeployed by novelists within free indirect style or internal monologue? The article begins by distinguishing four broad modes in which fictional works refract the world of cultural policy, and then analyses in more fine-grained detail two novels by the leading French writer Michel Houellebecq.